Co-control of multi-pollutants and CO2 based on extended life cycle assessment in electrolytic manganese industry - Ruichen Wang; Zhe Bai; Dandan Liu; Jingyang Liu; Zhiguo Yuan; Chunge Dang; Feilong Zhang (Resources, Environment and Sustainability)
The electrolytic manganese metal (EMM) industry has long been restricted because of associated heavy pollution and high CO2 emissions. In this study, an extended life cycle assessment (LCA) was conducted on the entire process of EMM production and an integrative decision-making framework was developed for the co-abatement of multiple pollutants and CO2, including emissions accounting, program design, and co-abatement economic benefits assessment. In the extended LCA that additionally considers the electric power supply and manganese residue treatment, the CO2 emissions from EMM production increased by 173% and the equivalent pollutant loads decreased by 85%. A technical guideline consisting of 16 co-control measures was formulated based on capacity adjustment, energy structure optimization, production management, and technical equipment upgrading. After eliminating the overlapping abatement effects among measures, this scheme achieved a cumulative abatement potential of 35.3% for CO2 and 96.3% for the equivalent pollutants. The co-econijranking results show that technologies based on the concepts of source reduction and resource recycling are more environmentally friendly and cost-efficient. Sensitivity analysis proved that the results were robust. This study enriches the theory of co-control of emissions and provides an efficient and credible methodology and practical reference for policymakers and industrial enterprises.